O tratamento psicanalítico do bebê com risco de autismo: uma clínica ao avesso? - Isabela Santoro Campanario (2013)
We start with preliminary questions about psychoanalytic treatment to babies at risk of autism. What subject status is possible for them? We continue dedicating ourselves to deepen the concept of drive approached by Lacan (1964). We write about the operations of alienation and separation. We bring the concept of holófrase and its incidence in infancy. We address the primacy of invocatory drive in the constitution of the subject and the music of speech. We work on the assumption of subject matter in the passage of the infant to the speakingbeing. We bring the risk indicators for child development (IRDI). We refer to the question of the structure of autism. Our work: is it anticipation or prevention? Psychogenesis or organogenesis? We make brief reference to transitivism. We point that draws attention to pain felt by the family of these children, a devastating pain. We make a journey through the concept of devastation. We bring the concept of joy and their implication in the constitution of the subject. We propose be acting in accordance with the so-called "psychoanalysis in reverse", which deals with the child in a position of object and allows these children to be subject. We bring three cases in children in mother-infant psychoanalysis with excellent results seem to indicate that other structural outputs were possible for these patients. However, this is a question, because patients are still being developed